2012
DOI: 10.1371/journal.pone.0051344
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Deficits in Long-Term Potentiation in the Adult Dentate Gyrus with 2nd Trimester Ethanol Consumption

Abstract: Ethanol exposure during pregnancy can cause structural and functional changes in the brain that can impair cognitive capacity. The hippocampal formation, an area of the brain strongly linked with learning and memory, is particularly vulnerable to the teratogenic effects of ethanol. In the present experiments we sought to determine if the functional effects of developmental ethanol exposure could be linked to ethanol exposure during any single trimester-equivalent. Ethanol exposure during the 1st or 3rd trimest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 81 publications
0
22
1
Order By: Relevance
“…Recent studies suggest that the long-lasting progenitors within the adult SGZ originate from a distinct population of neural stem cells within the ventral hippocampus generated during the perinatal period [51]. Synaptic input from the entorhinal cortex begins during late gestational periods in the rodent and continues to reach adult levels by postnatal day 25 in the rat [52]. Clearly, alcohol exposure during late gestation vs. early postnatal periods could influence distinct aspects of dentate development that lead to long-lasting deficits in neurogenesis that may manifest with distinct characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that the long-lasting progenitors within the adult SGZ originate from a distinct population of neural stem cells within the ventral hippocampus generated during the perinatal period [51]. Synaptic input from the entorhinal cortex begins during late gestational periods in the rodent and continues to reach adult levels by postnatal day 25 in the rat [52]. Clearly, alcohol exposure during late gestation vs. early postnatal periods could influence distinct aspects of dentate development that lead to long-lasting deficits in neurogenesis that may manifest with distinct characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal alcohol exposure results in decreased dentate LTP [37], [52], [65], [66], decreased expression of both NR1 and NR2B NMDA receptor subunits [67], and decreased NMDAR1 expression [68], [69]. GABA receptor expression and activity is also altered by prenatal alcohol exposure in rodents [70], [71].…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is a preferentially selective and dose-dependent effect on the foetal dentate gyrus in response to pre-natal alcohol exposure, with changes exhibited in the density and/or number of dentate gyrus granule cells and with none of these alterations being observed when the exposure period does not include the third trimester-equivalent. In addition, rodent studies using other modalities, such as magnetic resonance imaging and behavioural testing, to evaluate the hippocampus have also found that change in volume may not be a sensitive indicator of pre-natal alcohol exposure, but that functional deficits and surface and shape changes are present that indicate damage does indeed occur [3537]. The findings from this study utilizing unbiased stereologic analysis highlight the need to critically evaluate the sensitivity as well as specificity of screening methods being developed to assess injury from prenatal alcohol exposure.…”
Section: Discussionmentioning
confidence: 99%
“…EPIDEMIOLOGY AND CLINICAL MANAGEMENT OF VISCERAL OBESITY exposed to ethanol during this period (Clements, Girard, Ellard, & Wainwright, 2005;Hunt, Jacobson, & Torok, 2009;Thomas, Weinert, Sharif, & Riley, 1997;Thomas et al, 2008;Tiwari & Chopra, 2011;Zink et al, 2011); however, this has not been observed in all cases (Zink et al, 2011). Regarding synaptic plasticity, studies revealed no significant effect in the CA1 hippocampal region (Bellinger, Bedi, Wilson, & Wilce, 1999;Byrnes, Richardson, Brien, Reynolds, & Dringenberg, 2004) or the dentate gyrus (Helfer et al, 2012). In our laboratory, we recently examined the effect of ethanol exposure in vapor chambers during the first week of life in rats.…”
Section: Synaptic Plasticitymentioning
confidence: 98%
“…In the dentate gyrus, in vivo and in vitro electrophysiological studies have also demonstrated that developmental ethanol exposure alters long-term potentiation (LTP) and that exposure during the second trimester has the greatest impact on this synaptic plasticity mechanism (Christie et al, 2005;Helfer, White, & Christie, 2012;Sutherland, McDonald, & Savage, 1997). A recent study with rats examined the effect of ethanol consumption during pregnancy (voluntary drinking; BAL = 0.08 g/dl) and found deficits in hippocampal-dependent memory in adult offspring using the Morris water maze and contextual fear-conditioning tasks .…”
Section: Synaptic Plasticitymentioning
confidence: 99%